Effect of Lining Materials on Shear Bond Strength for Composite Restorations In Vitro - Feraz Caneppele, Taciana Marco [UNESP]; Bresciani, Eduardo [UNESP]; Da Silva Avila, Daniele Mara [UNESP]; Barcellos, Daphne Camara [UNESP]; Pucci, Cesar Rogerio [UNESP] (Quintessence Publishing Co Inc, 2017)
This study evaluated the influence of liner agents placed under resin composite restorations on shear bond strength (SBS) to dentin. A total of 40 extracted bovine incisors were used. Enamel surfaces were ground to expose a flat dentin area of 7 mm in diameter. Teeth were divided into four groups according to tested liners: Group 1 (control) used no liner; Group 2 used a resin-modified glass-ionomer cement liner (Vitrebond Plus, 3M ESPE); Group 3 used a lightactivated calcium hydroxide resin liner (Ultra-Blend Plus, Ultradent); and Group 4 used a polyacrylic acid surface treatment + conventional glass-ionomer cement liner (Vidrion F, SSWhite). All groups were subjected to bonding procedures with Single Bond (3M ESPE) and 4-mm-thick buildups of resin composite were fabricated. Artificial aging was performed, and the specimens were submitted to mechanical shear testing. One-way analysis of variance (ANOVA) revealed significant differences among liners (P =.00). Group 4 showed the highest SBS. Group 1 showed significantly higher mean SBS compared with Group 3. Results showed that SBS is improved when using polyacrylic acid surface treatment + conventional glass-ionomer cement and decreased when using light-activated calcium hydroxide when compared with no liner. Polyacrylic acid surface treatment + conventional glass-ionomer cement as a liner placed under adhesion surface can improve the shear bond strength between dentin and resin, while light-activated calcium hydroxide resin should be used restrictedly in very deep cavities, because they may reduce the bond strength of the restoration submitted to masticatory forces and temperature changes in the oral environment.